Makroekonomski učinki proizvodnje in predelave lesa listavcev - Arnič, Domen (Les (Ljubljana), 2023)
As far as the utilization of the value-added potential of hardwood assortments is concerned, we have considerable reserves in Slovenia. These could be exploited mainly by increasing the economic use of roundwood in Slovenia and by developing more technologically advanced processing methods for roundwood. The aim of this paper is to assess the untapped potential of the forest-wood chain in Slovenia using input-output models, focusing on the use of hardwood. For the whole forest-wood chain, we assessed the existing situation and tested five scenarios for the improvement of the forest-wood chain in Slovenia. We developed a national input-output model to evaluate possible scenarios for the future development of the wood-based bioeconomy. The results of scenario analysis of the input-output model show that the Slovenian wood-based bioeconomy can achieve up to 20% higher production value, a 24% increase in employment and 19% increase in household income in the future through restructuring of economic activities. In the paper, we discuss how upgrading the forestry and wood-processing industry (according to the defined scenarios) could be achieved by increasing the processing capacity of hardwoods and provide recommendations for decision makers.
Keywords: forest- and wood-based bioeconomy; gozdno-lesno biogospodarstvo; hardwoods utilization; input-output model; input-output models; lesnopredelovalna panoga; mobilizacija lesa listavcev; mobilization of hardwoods; raba lesa listavcev; scenarijska analiza; scenario analysis; wood processing industry